Implementasi Desain Pembelajaran dalam Menunjang Keberhasilan Belajar Siswa di SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Aulia, Rahmatul; Nurafifah, Vianti Dinda; Putri, Ratasya Salsabilla (ANWARUL, 2023)
The purpose of a lesson is to change and increase the knowledge of students. These objectives will be maximally achieved if accompanied by good learning planning. The learning model is one of the aspects that influence student success. This study aims to find out how teachers at SD Negeri Empang Bahagia 3 apply learning models for students to support their success. the method used is a qualitative method. The results of this research are that in supporting the success of students the teachers apply the PBL method in learning, but the teachers also complain because the learning resources are only for them, and also that the existence of lesson plans does not help much in carrying out learning activities.